1985
DOI: 10.1002/pssa.2210890204
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Influence of Mechanical Stresses on the Kinetics of Crystallization of Ion-Implanted Silicon Layers under Pulse Heating

Abstract: The method of numerical simulation on two‐layer structures such as a‐SiSi and a‐SiSiO2 is used to study the influence of mechanical stresses on the start temperature of self‐sustaining crystallization of an amorphous film, on the waiting time for the start of crystallization (or melting) t0, and on the expected time of film crystallization tn which is compared to the duration of a heating pulse. In case of simulation of the transformation kinetics the energy of strain field of a lattice during the doping is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The sizes of the crystalline domains were from 3 to 30 nm. This indicated that the silicon nanobond was a mixture of amorphous silicon and nanocrystalline silicon and that the silicon nanocrystals grew in the amorphous silicon part and mechanical stress can induce the crystallization of amorphous silicon [13].…”
Section: Silicon Nanobond Composed Of Amorphous Silicon and Nanoscale...mentioning
confidence: 99%
“…The sizes of the crystalline domains were from 3 to 30 nm. This indicated that the silicon nanobond was a mixture of amorphous silicon and nanocrystalline silicon and that the silicon nanocrystals grew in the amorphous silicon part and mechanical stress can induce the crystallization of amorphous silicon [13].…”
Section: Silicon Nanobond Composed Of Amorphous Silicon and Nanoscale...mentioning
confidence: 99%
“…The sources of the mechanical strain are the following: (i) radiation defects and amorphous regions [1][2][3]; (ii) temperature gradients during annealing [4,5]; (iii) difference between the covalent radii of dopant atoms in substitutional positions in the crystal lattice and substrate atoms (misfit strain) [6]. The sources of the mechanical strain are the following: (i) radiation defects and amorphous regions [1][2][3]; (ii) temperature gradients during annealing [4,5]; (iii) difference between the covalent radii of dopant atoms in substitutional positions in the crystal lattice and substrate atoms (misfit strain) [6].…”
Section: Introductionmentioning
confidence: 99%